1996
DOI: 10.1111/j.2042-3306.1996.tb05034.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses in nonheat acclimated horses performing treadmill exercise in cool (20°C/40%RH), hot dry (30°C/40%RH) and hot humid (30°C/80%RH) conditions

Abstract: Summary The aim of the present study was to determine the effect of different environmental conditions on physiological response to exercise. Four winter acclimatised, nonheat acclimated horses of different breeds were exercised at 20°C/40%RH (CD), 30°C/40%RH (HD) and 30°C/80%RH (HH). The exercise test was designed to represent the structure and intensity of a One star Speed and Endurance test (competition exercise test [CET]). All 4 horses were able to complete the full CET (60 min + 30 min active recovery) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 44 publications
2
60
1
4
Order By: Relevance
“…In this case, breathing frequency was not combined with stride frequency (Art et al 1990). The increase in breathing frequency could be a consequence of the increase in blood lactate concentration (Erickson et al 1991;McDonough et al 2002) and/or hyperthermia (Marlin et al 1996) during high speed repetitions. This is consistent with the increase in HR and decrease in RMSSD observed during exercise bouts.…”
Section: Hfhpectral Peakmentioning
confidence: 99%
“…In this case, breathing frequency was not combined with stride frequency (Art et al 1990). The increase in breathing frequency could be a consequence of the increase in blood lactate concentration (Erickson et al 1991;McDonough et al 2002) and/or hyperthermia (Marlin et al 1996) during high speed repetitions. This is consistent with the increase in HR and decrease in RMSSD observed during exercise bouts.…”
Section: Hfhpectral Peakmentioning
confidence: 99%
“…In addition the results, as well as being influenced by the rider, can be influenced by the terrain 5 and other environmental factors 6 , particularly if the test used is not of short duration. A number of field-based tests have been described, but they often rely on the availability of measured tracks and large, open spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Horses generate considerable internal heat burdens when exercising over long periods of time, particularly under hot and/or humid conditions (Foreman et al 1995;Geor et al 1995Geor et al , 2000Marlin et al 1996;Kohn et al 1999a). Data generated before the 1996 Atlanta Olympic Summer Games showed that multiple applications of nearly-ice-cold water to the horse's dorsum was a superior method of cooling post exercise compared to the conventional use of water baths of ambient temperature (Williamson et al 1995;Foreman et al 1996b;Kohn et al 1999b).…”
Section: Introductionmentioning
confidence: 99%